Karakteristik Dan Rancang Bangun Ekonomi Islam - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
In general, marketing is considered as a place for profit-earners, tricky people, vendors who tempt people's desires. Therefore many consumers are swallowed up by bad people, but if we implement Islamic systems in marketing then things like that won't happen. Basically, for Muslims the Prophet Muhammad SAW has taught us how the Islamic marketing system. However, because the community has rooted in conventional marketing systems, the Islamic marketing system is less well known. This is also a lesson for us to be able to re-introduce and make the marketing system develop among the people. In general, syariah marketing is a strategic business discipline that directs the process of creating, offering and changing the value of the initiator to its stake holders which in the whole process are in accordance with the agreements and principles of muamalah in Islam. This means that in Syariah marketing, the entire process, both the creation process, the bidding process, and the process of changing values ​​- there must be no conflict with sharia principles.